Penerapan Model PjBL Terhadap Hasil Belajar IPAS Kelas IV SD Negeri Mranggen 3 - Indah Nur Fauziyah; Kartinah Kartinah; M Yusuf Setia Wardana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to determine the application of the Project Based Learning model to science learning outcomes at SD Negeri Mranggen 3. This research was a quasi-experimental design study with a nonequivalent pretest-posttest control group design. The sample in this study were students of class IVA and IVB. Data collection was carried out by means of tests and non-tests. Data analysis techniques with normality, homogeneity, and t-test. The research results obtained from the initial data stated that the sample came from a population that was normally distributed and homogeneous. The requirements test using the t-test yields tcount = 2.444 and the coefficient is significant at the 5% level and db = 48, so ttable = 2.011 so the value of tcount > ttable. It can be concluded that the learning outcomes in class IV SD Negeri Mranggen 3 after using the Project Based Learning model are better than learning outcomes using conventional models.